1981
DOI: 10.1159/000250217
|View full text |Cite
|
Sign up to set email alerts
|

Problems with Commercial Formulations of 8-Methoxypsoralen

Abstract: Plasma concentrations of 8-methoxypsoralen were measured in 8 psoriatic patients after administration of two commercial solid formulations and of an 8-methoxypsoralen solution. Systemic availability as measured by the area under the concentration versus time curve was much higher for the solution than for the two commercial formulations. For the solid formulations, a large inter- and intraindividual variation in plasma concentrations was found and in many cases no plasma levels could be measured. Administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1983
1983
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Stolk et al (1980) were the first to demonstrate that the area under the serum concentration-time curve (AUCo_4h) could be significantly increased by administering methoxsalen as an aqueous solution instead of as a powder in a gelatin capsule. Several authors have confirmed this observation, namely that administration of methoxsalen in soft gelatin capsules containing the drug in solution leads to higher serum concentrations than micronised powder in hard gelatin capsules or in tablets (Honigsmann et al 1982;Langner & Wolska 1981;Monbaliu et al 1981;Nitsche et al 1981).…”
Section: Fundamental Pharmacokinetic Propertiesmentioning
confidence: 89%
“…Stolk et al (1980) were the first to demonstrate that the area under the serum concentration-time curve (AUCo_4h) could be significantly increased by administering methoxsalen as an aqueous solution instead of as a powder in a gelatin capsule. Several authors have confirmed this observation, namely that administration of methoxsalen in soft gelatin capsules containing the drug in solution leads to higher serum concentrations than micronised powder in hard gelatin capsules or in tablets (Honigsmann et al 1982;Langner & Wolska 1981;Monbaliu et al 1981;Nitsche et al 1981).…”
Section: Fundamental Pharmacokinetic Propertiesmentioning
confidence: 89%
“…Oral crystalline 8-MOP in tablet (27,28) crystalline 8-MOP in capsule (29)(30)(31) solution, aqueous (28,32) solution, in 20% aqueous ethanol (31) dissolved, in oil-in-water emulsion (30) micronized 8-MOP in tablet (21) micronized 8-MOP in hard gelatin capsule (30,(32)(33)(34)(35)) dissolved 8-MOP in soft gelatin capsule (29,31,(33)(34)(35) Topical aqueous bath (36)(37)(38) bathing suit soaked in 8-MOP aqueous solution (39) solution in isopropanol:water (40,41) aqueous gel (propylene glycol 10%, carbomer 934P 1%) (42) aqueous emulsion (7% 1,2-propylene glycol) (41) hydrophilic polyethylene glycol ointment (43) oil in water emulsion (43,44) oil and emulgator (Eutanol G) (41) solution in ethanol:acetone:propylene glycol 7:2:1 (45) oil solution (olive oil) (41) solution in hydrophilic petrolatum, mineral oil and wax (40) hydrophobic water in oil emulsion (43) cream (46) vaseline ointment (43) Rectal microenema (35,47) suppository (48,49) i.v. dissolved in isotonic saline solution (50) each individual patient and adjusting the 8-MOP dose and timing of the UVA dose accordingly.…”
Section: Route Of Administration Galenic Form Referencesmentioning
confidence: 99%
“…Le 8-MOP a été administré à jeun sous forme de solution [3], à trois reprises, aux doses resectives de 0,6, 0,45 et 0,3 mg/kg. Le p-8-MOP est déterminé par chromatographie en phase liquide sous haute pression [4] [6] 0,768 10,5 l/D PM /p-8-M O P [2] 0,691 18,1 1/DPM /log p-8-MOP [6] 0,738 15,7 log DPM/log p-8-MOP x log 1/DPM /log p-8-MOP ^0,764 13,4…”
Section: Méthodesunclassified